On Identities for Sequences of Binomial Sums with the Terms of Sequences {u_kn} and {v_kn} (European Journal of Pure and Applied Mathematics, 2017)
In this paper, considering a technique used in 4, and the sequences {u_{kn}} and {v_{kn}}, we derive the sequences {g_{kn}} and {h_{kn}}. Also with the aid of generating matrix for the terms of these sequences Â for a positive integer k, we derive some conbinatorial identities for the sequence {g_{kn}}.